Structural, optical, and luminescence properties of Cu2+-doped Ca-Li hydroxyapatite nanopowders prepared by mechanochemical synthesis. (21st August 2019) - Koutavarapu, Ravindranadh; Venkata Reddy, Ch; Rao, M C; Ravikumar, R V S S N; Cho, Migyung; Shim, Jaesool
Abstract: Novel luminescent phosphor materials have potential applications in lighting, display devices, and optical communication. In this study, novel Cu 2+ -doped calcium-lithium hydroxyapatite (CLHA) nanopowders were successfully fabricated by a simple mechanochemical technique. The synthesized samples were characterized by several microscopic and spectroscopic techniques. The hexagonal phase of the prepared sample was confirmed by x-ray diffraction results, and the average crystallite sizes were evaluated. Fourier transform infrared spectra demonstrated the formation of numerous vibrational modes ascribed to phosphate molecules and other hydroxyl groups. The morphologies of the Cu 2+ -doped CLHA nanopowders were investigated by scanning electron microscopy and transmission electron microscopy analyses. Optical absorption and electron paramagnetic resonance data indicated that the distortion of Cu 2+ in the host lattice corresponds to the tetragonal site symmetry. Photoluminescence (PL) spectra of the Cu 2+ -doped CLHA nanopowders revealed strong blue and weak green emission peaks. From the PL emission spectra, the chromaticity CIE parameters were evaluated, and the results indicated that the prepared phosphor materials may be useful for lighting and display devices.